“The Point is to Transform the Hood”: Learning from the Past to Build a School that Affirms the Humanity of Black and Brown Children - Noguera, Joaquín M. S. (Critical Education, 2025)
This paper draws from a critical ethnographic case study of the Roses in Concrete Community School (RiC) in East Oakland, California to explore their approach to repurposing a traditional school into a community responsive learning institution by operationalizing a critical humanist vision of education in a marginalized, urban community. The educator activists who founded RiC envisioned a school that would not only meet the needs of students and families, but act as an intervention and a catalyst for healing and transformation. Historiographic methods are used to examine how the founders conceived and implemented the design of RiC and to demonstrate how they drew upon the history of social movements in the Bay Area to design a school that they believed could meet the needs of poor and working-class Black and Brown children, and in doing so contributed to a longer, intergenerational struggle for justice.